Short-Step Adjustment and Proximal Compensatory Strategies Adopted by Stroke Survivors With Knee Extensor Spasticity for Obstacle Crossing - Huang, Shang-Jun; Yu, Xiao-Ming; Wang, Kuan; Wang, Le-Jun; Wu, Xu-Bo; Wu, Xie; Niu, Wen-Xin (Frontiers in Bioengineering and Biotechnology, 2020)
Stroke survivors adopt cautious or compensatory strategies for safe and successful obstacle crossing. Although knee extensor spasticity is a common independent secondary sensorimotor disorder post-stroke, few studies have examined the step adjustment and compensatory strategies used by stroke survivors with knee extensor spasticity during obstacle crossing. This study aimed to compare the differences in the kinematics and kinetics during obstacle crossing between stroke survivors with and without knee extensor spasticity, and to identify knee extensor spasticity-related differences in step adjustment and compensatory strategies. Twenty stroke subjects were divided into a spasticity group (n = 11, modified Ashworth scale (MAS) ≥ 1) and a non-spasticity group (n = 9, MAS = 0), based on the MAS score of the knee extensor. Subjects were instructed to walk at a self-selected speed on a 10-m walkway and step over a 15 cm obstacle. A ten-camera 3D motion analysis system and two force plates were used to collect the kinematic and kinetic data. During the pre-obstacle phase, stroke survivors with knee extensor spasticity adopted a short-step strategy to approach the obstacle, while the subjects without spasticity used long-step strategy. During the affected limb swing phase, the spasticity group exhibited increased values that were significantly higher than those seen in the non-spasticity group for the following measurements: pelvic lateral tilt angle, trunk lateral tilt angle, medio-lateral distance between the ankle and ipsilateral hip joint, hip work contributions, the inclination angles between center of mass and center of pressure in anterior-posterior and medio-lateral directions. These results indicate that the combined movement of the pelvic, trunk lateral tilt, and hip abduction is an important compensatory strategy for successful obstacle crossing, but it sacrifices some balance in the sideways direction. During the post-obstacle phase, short-step and increase step width strategy were adopted to reestablish the walking pattern and balance control. These results reveal the step adjustment and compensatory strategies for obstacle crossing and also provide insight into the design of rehabilitation interventions for fall prevention in stroke survivors with knee extensor spasticity.